Living up to the chatbot hype: The influence of anthropomorphic design cues and communicative agency framing on conversational agent and company perceptions. (August 2018) - Araujo, Theo
Abstract: Disembodied conversational agents in the form of chatbots are increasingly becoming a reality on social media and messaging applications, and are a particularly pressing topic for service encounters with companies. Adopting an experimental design with actual chatbots powered with current technology, this study explores the extent to which human-like cues such as language style and name, and the framing used to introduce the chatbot to the consumer can influence perceptions about social presence as well as mindful and mindless anthropomorphism. Moreover, this study investigates the relevance of anthropomorphism and social presence to important company-related outcomes, such as attitudes, satisfaction and the emotional connection that consumers feel with the company after interacting with the chatbot. Highlights: Human-like cues increase perceptions of mindless and mindful anthropomorphism. Social presence higher for human- (vs. machine-like) agent with intelligent frame. Human-like cues increase company emotional connection levels in service encounters. Social presence mediates effect of human-like cues on company emotional connection.